Clinical Characteristics and Outcomes of COVID-19 in Newborn and Infants - Lubis, Bugis Mardina (International Journal of Scientific Research and Management (IJSRM), 2021)
Objective: To describe the clinical and outcome of neonates born from women infected with COVID-19 while pregnant.Design : Our study was observational cohort studyMaterial and Methods: We identified all neonates born between April - October 2020 at RSUP H. Adam Malik Medan from mothers who tested positive for COVID-19 during childbirth.Result: From 122 deliveries mothers with suspected COVID-19, 43 (35.2%) mothers tested positive for COVID-19. All neonates were examined in the first 24 hours of life, and there were 5 (11.6%) neonates identified as positive for COVID-19. 2 (40%) neonates had symptoms of shortness of breath, and 1 (20%) had symptoms of fever. 2 (40%) neonates died.Conclusion: Given the lack of current research, vertical transmission cannot be confirmed or refuted. The existing literature does not support the prohibition of breastfeeding or the separation of mothers and newborns. Further evidence is needed to establish definite guidelines and recommendations